2014
DOI: 10.3109/02770903.2014.906608
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver knowledge and its relationship to asthma control among children in Saudi Arabia

Abstract: Although innovations are needed to help patients improve their adherence to treatment and to effectively utilize the benefits of contemporary asthma medications, we observe substantial knowledge-related problems in the asthma management of children in Saudi Arabia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 33 publications
3
23
1
Order By: Relevance
“…In addition to these important factors, there are other attributes to the magnitude of disease burdens such as socioeconomic status, number of siblings, knowledge of caregivers, and income. [ 37 38 39 40 41 42 ] Consequently, many asthma patients continue to be underdiagnosed, undertreated, and at risk of acute exacerbations resulting in missed work or school, increased use of expensive acute healthcare services, and reduced quality of life. [ 43 44 45 ] A study by Al-Kabbaa et al .…”
Section: Methodsmentioning
confidence: 99%
“…In addition to these important factors, there are other attributes to the magnitude of disease burdens such as socioeconomic status, number of siblings, knowledge of caregivers, and income. [ 37 38 39 40 41 42 ] Consequently, many asthma patients continue to be underdiagnosed, undertreated, and at risk of acute exacerbations resulting in missed work or school, increased use of expensive acute healthcare services, and reduced quality of life. [ 43 44 45 ] A study by Al-Kabbaa et al .…”
Section: Methodsmentioning
confidence: 99%
“…In another Nigerian study, mothers constituted 88.5% of the caregivers with the mean age of the caregivers being 38.6 ± 9.1 years (20). Furthermore, almost all the caregivers (97.5%) in a study conducted in Riyadh, Saudi Arabia, were the mothers of the children with a mean age of 35.2 ± 5.6 years (21). Another study that evaluated the association of QoL of caregivers of children with asthma severity and health-care utilization had most of the caregivers as mothers aged between 31 and 40 years old (22).…”
Section: Discussionmentioning
confidence: 97%
“…Many children with asthma avoid or are prevented by their caregivers from engaging in physical activity or strenuous activities. This might interfere in the assessment of asthma control parameters, relevant for evaluating the impact of asthma on the daily activities of a child (21,35). Caregivers might want to avoid the burden that comes with managing asthma exacerbations by limiting their child's physical activity, but this could affect the overall development of the child (36).…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out in Saudi Arabia found that the prevalence of uncontrolled asthma was substantially higher among children of caregivers who agree that it is not good for children to use an inhaler for too long and that inhalers can affect or damage heart. 10 Uncontrolled asthma is associated with parental beliefs concerning the use and potential side effects of asthma medication, which emphasizes the need to focus efforts to improve knowledge and positively influence parent´s perception with respect to inhaled therapy. 11 Thirteen parents (11%) consider pMDI's/DPI's use less effective than the use of nebulizers.…”
Section: Discussionmentioning
confidence: 99%